2018
DOI: 10.1039/c8ra03911a
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of advances in diterpenoid alkaloids with cytotoxicity activities

Abstract: The important pharmacological activities and structural complexity of diterpenoid alkaloids have long stimulated strong scientific interest; some of these naturally abundant compounds have been reported to be highly promising for treating cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In addition to the Aconitum and Delphinium genera, Consolida is another genus in the Ranunculaceae family that is well known for its characteristic DA components. 11,14 DAs are unambiguously the most predominant and representative constituents of Consolida plants and have attracted much research interest since the beginning of the 20th century. 9 However, studies on the DA composition of Consolida plants increased only in the 1980s due to the difficulty associated with the structural iden-tication of DAs, which possess a fused polycyclic skeleton substituted with multiple oxygenated groups.…”
Section: Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the Aconitum and Delphinium genera, Consolida is another genus in the Ranunculaceae family that is well known for its characteristic DA components. 11,14 DAs are unambiguously the most predominant and representative constituents of Consolida plants and have attracted much research interest since the beginning of the 20th century. 9 However, studies on the DA composition of Consolida plants increased only in the 1980s due to the difficulty associated with the structural iden-tication of DAs, which possess a fused polycyclic skeleton substituted with multiple oxygenated groups.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Although no species of Consolida are traditionally used to treat cancer, several studies have revealed that the crude extracts and isolated compounds of Consolida plants possess certain 95 which might be attributed to the high content of some DAs with cytotoxic activities in the C. orientalis extracts. 17,96 De Inés et al evaluated the cytotoxic effects of 43 DAs (40 C 19 -DAs and 3 C 18 -DAs) on CHO cells and several tumor cell lines, including CT26 (murine colon adenocarcinoma), SW480 (human colon adenocarcinoma), HeLa, SkMel25 (human melanoma) and SkMel28 (human malignant melanoma). 97 As shown in Table 7, 13 of the tested alkaloids that have been found in Consolida plants produced a cytotoxic effect on the different cell lines (MICs < 100 mg mL À1 ).…”
Section: Antitumor Activitymentioning
confidence: 99%
“…62 These FFAs could be bonded to C 19 -DAs through ester exchange reaction to generate lipo-alkaloids, a kind of DAs consist of a C 19 -DAs skeleton and one or two fatty acid side chains substituted at C-8 or C-14, which have been reported to exhibited impressive bioactivities. 10,63…”
Section: Free Fatty Acids (Ffas)mentioning
confidence: 99%
“…[6][7][8] To date, a number of reviews considering various aspects of DAs in Aconitum plants have been published. 9,10 Nevertheless, the non-alkaloidal natural constituents in Aconitum plants have also received researchers' strong interests. Recently, various kinds of non-alkaloidal constituents, including avonoids, phenylpropanoids, phenolics and acids, terpenoids, steroids, free fatty acids (FFAs) and polysaccharides, have been reported to be isolated from the Aconitum plants.…”
Section: Introductionmentioning
confidence: 99%
“…6.1 Anticancer activityA certain number of natural DAs have been reported to possess antiproliferative activities against various human cancer cell lines, indicating their great potential as new drugs for treating the corresponding cancers 133. New DAs along with known DAs from Delphinium plants have also been reported to have in vitro anticancer activities (Table 1).…”
mentioning
confidence: 99%